Economic Cost of the Feed - in - Tariff (FiT) in Thailand - Tharisung, Kaesinee (International Journal of Energy Economics and Policy, 2020)
This study aims to determine how much of an economic loss results from the FiT policy and to provide such information to the government, which in turn sets policy for future decisions. Findings from a SUR estimation show that the supply of each energy source does not respond to the purchase price, except in the case of natural gas. Increases in the purchase price of natural gas increases the quantity used to produce electricity by natural gas at a significance level 1 percent. The FiT policy is found to create an economic loss that comes from violating the law of one price and from ignoring an externality cost, amounting to 46.67 and 356.44 billion per year, respectively. Therefore, this study suggests that the Thai government should adjust the electricity purchase price by setting the purchase price by following the law of one price and thus reflecting the full cost pricing in power generation. Keywords: Economic Loss, SUR estimation, FiT policy, Law of One Price, full Cost Pricing JEL Classifications: Q41, Q48, Q51 DOI: https://doi.org/10.32479/ijeep.9367